PENGETAHUAN SISWA SMP KELAS VIII DALAM MEMECAHKAN MASALAH MATEMATIKA NON GEOMETRI BERDASARKAN LEVEL 2 PERKEMBANGAN BERPIKIR VAN HIELE - Rosanti, Arminda Sari; Muh. Rizal, Muh. Rizal; Ismaimuza, Dasa (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The purpose of this study was to obtain a description of the knowledge of eighth grade students in solving mathematical problems of Â non geometry based on the level of development of the Van Hiele thinking. This study used qualitative methods with qualitative descriptive approach based on the troubleshooting steps proposed by Krulik and Rudnick. The results show that knowledge of the subjectis at level 2Van Hiele thinking developments in solving the mathematical problem of non geometry is as follows: (1) knowledge on the stage of reading and thinking about the problemis knowledge of the phrase "statement" and the sentence "question", (2) knowledge on stage explore and plan for solving the problemis the knowledge of how to mix between elimination and substitution, elimination method and the substitution method, (3) knowledge at the stage of selecting a solution strategy isknowledge of the steps of the chosen strategies, (4) Knowledge on the stage of searching for an answer is the knowledge of the implementation of the plan involves the knowledgeof equation, similartribes, operations on the algebra, and integer operations, (5) knowledge on the stage of reviewing the answer are subjec to observation at a previous job, then do a recalculation by means of substitution and then compare the results obtained.